Socio-Emotional and Developmental Impacts of the COVID-19 Pandemic on Young Children – A Systematic Review (2020-2025) - Varga, László; Zsámboki, Réka Kissné (Journal of Cultural Analysis and Social Change, 2026)
This systematic review synthesized evidence from 13 studies (2020–2025) focusing on the impact of the COVID-19 pandemic on the socio-emotional development, school readiness, and behavioral outcomes of young children, as well as related parental and environmental factors. Across diverse designs and samples, findings indicated predominantly negative outcomes, including increased anxiety, aggression, emotional symptoms, language delays, reduced socialization, and declines in school readiness and life skills. However, some studies highlighted resilience, with reduced socio-emotional risks in certain cohorts, and benefits from enriched kindergarten environments and outdoor play. Parental emotional intelligence, coping, resilience, and burnout were strongly predictive of children’s outcomes, while socioeconomic status moderated the protective effects. Although pandemic repercussions were evident across all income levels, the impacts on executive functioning and emotional well-being varied. Overall, while children demonstrated adaptability, the pandemic intensified developmental vulnerabilities, underscoring the need for interventions that strengthen parental support, promote equitable access to enriching environments, and prioritize socio-emotional learning.